High-fat diet and palmitic acid amplify airway type 2 inflammation - Dimasuay, Kris Genelyn; Berg, Bruce; Schaunaman, Niccolette; Holguin, Fernando; Winnica, Daniel; Chu, Hong Wei (Frontiers in Allergy, 2023)
Metabolic dysfunction such as elevated levels of saturated fatty acids (SFA) may play a role in obese asthma, but its contribution to airway inflammation remains unclear. We sought to determine the role of high-fat diet (HFD) and palmitic acid (PA), a major form of SFA, in regulating type 2 inflammation. Airway samples from asthma patients with or without obesity, mouse models and human airway epithelial cell culture were utilized to test if SFA amplify type 2 inflammation. Asthma patients with obesity had higher levels of airway PA than asthma patients without obesity. HFD increased the levels of PA in mice, and subsequently enhanced IL-13-induced airway eosinophilic inflammation. PA treatment amplified airway eosinophilic inflammation in mice that were previously exposed to IL-13 or house dust mite. IL-13 alone or in combination with PA increased dipeptidyl peptidase 4 (DPP4) release (soluble DPP4) and/or activity in mouse airways and human airway epithelial cells. Inhibition of DPP4 activity by linagliptin in mice pre-exposed to IL-13 or both IL-13 and PA increased airway eosinophilic and neutrophilic inflammation. Our results demonstrated the exaggerating effect of obesity or PA on airway type 2 inflammation. Up-regulation of soluble DPP4 by IL-13 and/or PA may serve as a mechanism to prevent excessive type 2 inflammation. Soluble DPP4 may have the therapeutic potential in asthma patients with obesity who have an endotype with mixed airway eosinophilic and neutrophilic inflammation.